The population attributable fraction of occupational COPD among Danish women. Issue 2 (18th May 2017) - Würtz, Else; Schlünssen, Vivi; Malling, Tine; Hansen, Jens Georg; Omland, Øyvind
Women have a different clinical expression of chronic obstructive pulmonary disease (COPD) [1] and are more prone to developing COPD than men with similar exposures. These findings have been ascribed variously to a different susceptibility to tobacco smoke and anatomic, hormonal and behavioural differences [2]. Women have been shown to perform work with lower exposures than men within the same occupation and industry [3]. Despite these obvious and important gender differences, few studies have focused on occupational COPD in women. The population attributable fraction (PAF) for COPD due to occupational exposure to vapour, gases, dust and fumes (VGDF), irrespective of sex, is ∼15% [4, 5]. However, to our knowledge, no estimates have been published that focus solely on women. We thus analysed cross-sectional data among 1626 Danish women aged 45–84 years in relation to occupational COPD. The analyses add important information to our previously published population-based study [6]. The PAF of occupational COPD among Danish women http://ow.ly/CEmy308XEgl